Early post-transplant urinary tract infection epidemiology and risk factor - Muhammed Suhaib Subhi Fakhri Almufti (Advanced Medical Journal)
Background and objectives: Renal Transplantation became the most successful management for end stage renal failure; postoperative urinary tract infection is the most common complication. The aim is to evaluate the outcome and risk factors of posttransplant urinary tract infection.